Results in the Latin America and Caribbean Region 2015, Volume 5 - World Bank (Washington, DC, 2015)
In the past decade, Latin America and the Caribbean has achieved impressive social and economic successes. For the first time in history, more people are in the middle class than in poverty. Inequality, although still high, declined markedly. Growth, jobs and effective social programs have transformed the lives of millions. In a striking departure from the crisis-prone Latin America of the past, the region has shown it is better prepared to weather the brunt of the global economic slowdown. Now, the region faces the challenge of maintaining and expanding its hard won gains in an adverse context of low growth. This is caused in part by a decrease in commodity prices and reduced economic activity in major commercial partners such as China. In such a scenario, achieving development results - and learning from them - becomes more important. This publication showcases stories about people and how their lives have been improved through better health and education, youth employment, disaster recovery and preparedness, infrastructure, and more.